2021
DOI: 10.1038/s41598-021-87970-w
|View full text |Cite
|
Sign up to set email alerts
|

Promoter switching in response to changing environment and elevated expression of protein-coding genes overlapping at their 5’ ends

Abstract: Despite the number of studies focused on sense-antisense transcription, the key question of whether such organization evolved as a regulator of gene expression or if this is only a byproduct of other regulatory processes has not been elucidated to date. In this study, protein-coding sense-antisense gene pairs were analyzed with a particular focus on pairs overlapping at their 5’ ends. Analyses were performed in 73 human transcription start site libraries. The results of our studies showed that the overlap betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 69 publications
2
5
0
Order By: Relevance
“…Similarly, a positive expression correlation was found when data was divided according to the tumor type and the organ system (Supplementary materials, Figure S1A and S1B). These results confirm our previous report, demonstrating a positive correlation of expression of 5’ overlapping genes (Rosikiewicz et al 2021).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Similarly, a positive expression correlation was found when data was divided according to the tumor type and the organ system (Supplementary materials, Figure S1A and S1B). These results confirm our previous report, demonstrating a positive correlation of expression of 5’ overlapping genes (Rosikiewicz et al 2021).…”
Section: Resultssupporting
confidence: 93%
“…One possible consequence is that TI may cause a decrease in the level of gene expression, however, there are studies that do not confirm such a pattern (C. H. Chen, Pan, and Lin 2019; Ning et al 2017; Zhou and Blumberg 2003). Our previous analyses have shown that expression of genes utilizing an TSS which is overlapping at the 5’ end with gene on the opposite DNA strand, is on average higher than when the same genes use only none overlapping TSSs (Rosikiewicz et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations